THE YIELD OF SWEET CORN AND POPCORN DURING PERMANENT CULTIVATION AND IN CROP ROTATIONS - Маслиёв, С. В. (Scientific Progress & Innovations, 2014)
The results of long-term field experiments of the yield of sweet corn cobs and popcorn grains of various sorts and hybrids, depending on the precursors in field and vegetable crop rotations and also permanent sowing are shown. The recommendations on applying mineral fertilization and terms of sowing are given. It is found that the best precursors for these subspecies of corn in field crop rotations are a mixture of peas and oat for green nutriment and winter wheat after steam, and in vegetable crop rotations the best are cucumbers, onions, tomatoes, early potatoes and zucchini, after which the yield of sweet corn cobs reaches 8,5 -9,5 t / ha and popcorn grains – 2,2-2,9 t / ha.